Ethyl oligo-silicates with strong acid heterogeneous polymeric catalysts - Bevara, Madhusudana Rao; Bhongale, Sunil Sitaram; Bhosle, Sonali Madhavrao; Chavan, Nayaku; Chelanattukizhakkemadath, Raman Rajan; Deokar, Sarika Babasaheb; Dhoble, Deepa Arun; Dwivedi, Mayank; Ghorpade, Ravindra V.; Harikrishna, Reghunathan; Dhanasekharan, Janakiraman; John, Aruldoss; et al. (WO2012056290 A1, 2012)
The present invention provides a process for the synthesis of ethyl silicate with varying silica concentration, by hydrolysing ethyl silicate in varying water concentration in the presence of sulfonated catalysts having a styrene-divinyl benzene backbone. The present invention further relates to the preparation of beaded crosslinked polymers containing sulfonic acid moieties having an interconnected pore structure and surface area up to 400 m2 /g.